2020
DOI: 10.1126/scisignal.aba3300
|View full text |Cite
|
Sign up to set email alerts
|

The purinergic receptor P2Y11 choreographs the polarization, mitochondrial metabolism, and migration of T lymphocytes

Abstract: T cells must migrate to encounter antigen-presenting cells and perform their roles in host defense. Here, we found that autocrine stimulation of the purinergic receptor P2Y11 regulates the migration of human CD4 T cells. P2Y11 receptors redistributed from the front to the back of polarized cells where they triggered intracellular cAMP/PKA signals that attenuated mitochondrial metabolism at the back. The absence of P2Y11 receptors at the front of cells resulted in hotspots of mitochondrial metabolism and locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 67 publications
2
25
0
Order By: Relevance
“…ATPγS, similar to ATP, is likely to induce internalization of the P2Y11 receptor. The lack of expression or functional P2Y11 receptor in the breast cancer cells reduces breast cancer migration, indicating the intrinsic activity of this receptor, as reported in other cellular systems [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…ATPγS, similar to ATP, is likely to induce internalization of the P2Y11 receptor. The lack of expression or functional P2Y11 receptor in the breast cancer cells reduces breast cancer migration, indicating the intrinsic activity of this receptor, as reported in other cellular systems [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 55%
“…P2Y11 is also involved in the anti-tumor process of ATP in prostate cancer DU145 cells [ 45 ]. Another study reported that over stimulation of P2Y11 with excessive extracellular ATP results in defective T cell migration [ 46 ]. Therefore, we explored the role of P2Y11 in the effect of ATPγS on breast cancer cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…In the continuation of their previous work, Ledderose et al studied the role of the purinergic receptor P2Y11 in the migration of human T lymphocytes (97). The P2Y11 receptor is a G-protein coupled receptor which, after binding of extracellular ATP, induces the production of the second messenger c-AMP, which stimulates protein-kinase A.…”
Section: Role Of P2x4 In T Cell Receptor Signaling and T Cell Migrationmentioning
confidence: 95%
“…P2Y 11 receptor expression is often associated with immune cells. P2Y 11 receptors have recently been shown to participate in the process of T cell migration by regulating mitochondrial metabolism [ 95 ]. In addition to T cells, which are components of the adaptive immune system, P2Y 11 receptor expression has repeatedly been reported to occur in innate immune cells [ 25 , 61 , 90 , 91 , 93 , 96 ].…”
Section: P2y 11 Receptormentioning
confidence: 99%